2005
DOI: 10.1105/tpc.105.032375
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis Homeodomain Transcription Factor, OVEREXPRESSOR OF CATIONIC PEROXIDASE 3, Mediates Resistance to Infection by Necrotrophic Pathogens

Abstract: The mechanisms controlling plant resistance to necrotrophic fungal pathogens are poorly understood. We previously reported on Ep5C, a gene shown to be induced by the H 2 O 2 generated during a plant-pathogen interaction. To identify novel plant components operating in pathogen-induced signaling cascades, we initiated a large-scale screen using Arabidopsis thaliana plants carrying the b-glucuronidase reporter gene under control of the H 2 O 2 -responsive Ep5C promoter. Here, we report the identification and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
119
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(130 citation statements)
references
References 65 publications
10
119
1
Order By: Relevance
“…3 C and D), an inhibitor of NADPH oxidase in both plant and animal tissues (20,29). The cumulative results indicated that AtPep1 requires H 2 O 2 for the transcription of PDF1.2, consistent with recently proposed pathways for JA͞ethylene signaling (28).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…3 C and D), an inhibitor of NADPH oxidase in both plant and animal tissues (20,29). The cumulative results indicated that AtPep1 requires H 2 O 2 for the transcription of PDF1.2, consistent with recently proposed pathways for JA͞ethylene signaling (28).…”
Section: Resultssupporting
confidence: 84%
“…3C). The production of active oxygen species has been associated with the signaling pathway of the innate immune response in plants (28). The induction of both H 2 O 2 and PDF1.2 by AtPep1 was blocked by first supplying the leaves with diphenylene iodominium chloride (DPI) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…B. cinerea infection assays were performed using either a spore suspension (2 3 10 5 spores mL 21 ) or colonized agar plugs as indicated in the text. The average lesion size (diameter) and plant decay were measured as described previously (Coego et al, 2005;Veronese et al, 2006).…”
Section: Plant Materials Vigs Experiments and Disease Assaysmentioning
confidence: 99%
“…The phenotypes of rst1 correlate with increased levels of JA-biosynthesis and responsive gene expression as well as elevated cutic-ular lipids. Increased resistance of the overexpressor of cationic peroxidase 3 (ocp3) mutant to B. cinerea and P. cucumerina is also COI1-dependent (Coego et al, 2005). PFT1, which encodes the MED25 subunit of Mediator, functions downstream of COI1 in A. brassicicola and B. cinerea defense (Kidd et al, 2009).…”
Section: Jasmonatementioning
confidence: 99%
“…Among these, WRKY33, WRKY70, ZFAR1, ERF1 and ERF104 are required for responses to B. cinerea (Mengiste et al, 2003; Lorenzo et al, 2004;AbuQamar et al, 2006;Zheng et al, 2006; Bethke et al, 2009). Genetic screens identifi ed other important TFs encoding MYB, AS1, and HD-Zip homeodomain proteins (Mengiste et al, 2003;Coego et al, 2005;Nurmberg et al, 2007). The transmission of signals from upstream pathogen recognition factors to the activation of plant defense responses via these TFs is poorly understood especially for responses to important necrotrophic fungi.…”
mentioning
confidence: 99%